The world experience in the organization and regulation of the powerlessness of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
"The article deals with foreign experience in the institution of bankruptcy with respect to its applicability in Kazakhstan, practices and mechanisms to improve the organization of insolvency in the kazakh economy."
Keywords: Poor organization; The process of bankruptcy